Association Between Gadget Use, Energy and Protein Intake, and Nutritional Status: A Cross-Sectional Study Among Senior High School Adolescents in Porong - Dwi Hari Rahmawati; Nuning Marina Pengge; Taufiqurrahman; Annas Buanasita (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Indonesia ranks fourth globally in internet users, with over 100 million smartphone users recorded in 2018, raising concerns about the impact of widespread gadget use on adolescents' lifestyle and nutritional health. This study aims to analyze the association between gadget use, energy and protein intake, and nutritional status among senior high school students in Porong. A descriptive-analytic study with a cross-sectional design was conducted at SMAN 1 Porong from September 2023 to February 2024, involving 60 tenth-grade students selected through simple random sampling. Data were collected using a validated gadget use questionnaire, anthropometric measurements (BMI), and a 2x24-hour dietary recall. Data were analyzed using SPSS, applying univariate and Spearman correlation tests. The results showed a significant correlation between gadget use duration and nutritional status (p = 0.002), while no significant relationships were found between energy intake (p = 0.439) or protein intake (p = 0.859) and nutritional status. Future research is recommended to involve larger sample sizes, adopt longitudinal designs, and include additional variables such as physical activity, sleep quality, and mental health to better understand the determinants of adolescent nutritional status.